PENGARUH RETRIBUSI SAMPAH, RETRIBUSI PARKIR DAN RETRIBUSI TERMINAL TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA PEKALONGAN - SE., M.Si, Drs Usamah (STIE Muhammadiyah Pekalonga, 2011)
Regional autonomy demands self-reliance in regional funding, the local government should optimize revenue to finance day-to-day activities of the area. In 2010, an increase in personnel expenditure rose to 99 percent and stagnant funding in other sectors. While acceptance of the PAD sector levies each year fluctuated annually, primarily to levy waste never reaches the target during the last 10 years. Parking levy does not reach the target by 2010 and increase revenue levy terminal after switching the location of the highway Dr, Soetomo street to the Gamers pantura streets in 2002. This study aimed to determine the effect of garbage fees, parking fees and terminal charges against PAD town of Pekalongan.The research method used is multiple regression analysis. The data sources used are secondary data in the form of reports and the realization of the target annual revenue from the years 2001-2010. The data obtained from the Dinas Pendapatan Pengelolaan Keuangan dan aset daerah (DPPKAD) town of Pekalongan. The results of this study showed each of the waste levy, parking fees and terminal charges no significant effect on PAD. While jointly levy garbage, parking fees and terminal charges have a significant effect on PAD. The results of this evaluation is expected to be material in terms of government revenue so that revenue levies can be further optimized.Wordkeys : PAD, waste levy, parking fees and terminal char